2020
DOI: 10.3390/agronomy10111822
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Microbiological Control Strategies against Botrytis cinerea Using Systemic Plant Resistance Activation

Abstract: Botrytis cinerea is a polyphagous necrotrophic fungus and is the causal agent of grey mold diseases in more than 1400 different hosts. This fungus causes serious economic losses in both preharvest and post-harvest—mainly in grape, strawberry, and tomato crops—and is the second most important pathogen worldwide, to our knowledge. Beneficial bacteria and fungi are efficient biocontrol agents against B. cinerea through direct mechanisms, such as parasitism, antibiosis, and competition, but also indirectly through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 143 publications
3
37
0
Order By: Relevance
“…Biological control agents such as Bacillus sp. and their metabolites have received a lot of attention as complementary or alternative methods to the use of conventional chemical fungicides [ 1 , 3 , 4 , 5 ]. In this study, we showed that the endophytic Bacillus velezensis Bvel1 can be used to control grey mold caused by B. cinerea .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biological control agents such as Bacillus sp. and their metabolites have received a lot of attention as complementary or alternative methods to the use of conventional chemical fungicides [ 1 , 3 , 4 , 5 ]. In this study, we showed that the endophytic Bacillus velezensis Bvel1 can be used to control grey mold caused by B. cinerea .…”
Section: Discussionmentioning
confidence: 99%
“…Botrytis bunch rot (grey mold) caused by the necrotrophic fungal pathogen Botrytis cinerea is a major disease of grapevines. Infection of ripening berries leads to large losses in the quantity and quality of both table and wine grapes, either in the field or under post-harvest storage conditions [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several pathogens and consequently new yeast species with the potential to be used as BCAs have recently been discovered and citations about their roles are reported here. However, this review was inspired by the scarcity of information related to the biocontrol activity of yeasts against Aspergillus spp., Penicillium spp., and Botrytis cinerea species—i.e., the three main causes of postharvest grape diseases [ 31 , 32 , 33 , 34 ]. Finally, the present work analyzes the relevant mechanisms underlying the antagonistic action of yeasts on the above-mentioned molds and presents a comprehensive table with reference material for a rapid and direct comparison.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the fungi Aureobasidium pullulans , Diaporthe sp., and Nigrospora oryzae inhibits the development of C. acutatum ( Landum et al, 2016 ). Useful fungi and bacteria limit the growth and development of pathogens by activating antagonistic mechanisms such as parasitism, antibiotics, and competition ( Poveda et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%